Arabic language as a foundation of Islamic civilization: the role of huffaz in building of Islamic civilization - Akhmetova, Elmira (2016)
This paper discusses the importance of language and learning in enhancing human society and civilization. it claims that Arabic language was a language of science and diplomacy for several centuries in Europe, culminating at the rise of Muslim Andalusia with many examples of great contributions of Muslim scholars to the rise of European civilization. Language is a tool of getting knowledge and many non-Arab Muslims learned Arabic through memorization.